Correlation between antioxidant effect mechanisms and polyphenol content of Rosa canina - (:unkn) unknown (MEDKNOW PUBLICATIONS & MEDIA PVT LTD, 2010)
Rosa canina L. is a member of Rosaceae family, which is well-known for its high phenolic contents. These compounds are known to possess antioxidant, antimutagenic and anticarcinogenic effects. However, they have yet to pass controlled clinical trials for efficacy, and their potential for prooxidant activity is an understudied field of research. In order to estimate the correlations between phenolic contents and antioxidant/proxidant effect mechanisms, different concentrations of R. canina fruit extracts were examined in this study. R. canina showed antioxidant activities at all concentrations with respect to the reducing power, hydrogen peroxide scavenging activity and superoxide anion radical scavenging (O-2(center dot-)) activity assays, whereas a negative correlation was observed with the metal ion chelating activity and free radical scavenging activity [1,1-diphenyl-2-picryl-hydrazil (DPPH) % inhibition] assays at higher concentrations with the phenolic content of R. canina. These results suggest that R. canina may act not only as an antioxidant, but also as a prooxidant with the effects depending on its concentrations..
Keywords: Antioxidant; phenolics; prooxidant; Rosa canina; CHEMICAL-COMPOSITION; OXIDATION; FLAVONOIDS; INHIBITION; PREVENTION; TURKEY; ANION; TEA